(untitled) (Research, Society and Development, 2020)
The objective of this article is to relate tourism and territorial innovation based on the association with gastronomy as a vector for tourism development. To fulfill the proposal, a literature review was carried out as a way to justify the theme presented based on scientific research. For that, initial concepts such as tourism, tourist destination, competitiveness, territory and innovation were discussed, selected from bases such as SCOPUS, Scielo and printed books. It is concluded that tourism associated with gastronomy is favorable as long as training and technical skills for the actors involved are strengthened and promoted, respecting culinary traditions and including innovation, allowing the inclusion of new technological processes in the search for a better final product, which it is food, considering the production of healthy and safe food, focusing on the sustainability and participation of the local community.